Pengaruh Sikap Dan Persepsi Terhadap Loyalitas Pelanggan Produk Aqua Di Agen Di Kecamatan Candipuro Kabupaten Lumajang - Fauzan Muttaqien; Sukma Ardi Firmandita (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
This study aims to determine the effect of attitudes and perceptions on customer loyalty of drinking water in the packaging of Aqua brand on Aqua agent in Candipuro subdistrict partially and simultaneously. The method used in this research is multiple linear regression. This research is a quantitative research by finding associative association that is causal or research that is asking about the relationship between two or more variables and causality. The analysis used in this research is multivariate analysis that is multiple linear regression analysis consist of 2 (two) independent variable and 1 (one) dependent variable, then sample size taken 10x3 variable = 30 sample member. Sampling method used in this research is non-probability sampling with purposive sampling technique. Meanwhile, the coefficient of determination (R Square) obtained is 0.383. This means 38.3% loyalty can be explained by attitude and perception variables, while the remaining 61.7% loyalty is influenced by other variables not examined in this study. Limitations of this study is to examine the effect of attitude and perception on customer loyalty, while other variables that can influence customer loyalty are expected to be investigated by the next researcher.